Two-photon decay enhanced even photon bundle emission - Biao Xiong; Qian Bin; Shi-Lei Chao; Ji-Bing Liu; Xin-You Lü (Physical Review Research)
Multiquanta emission holds significant value for quantum computing and quantum information processing. In this study, we aim to enhance multiphoton bundle emission by introducing two-photon decay into cavity quantum electrodynamics systems. By implementing parity protection induced by two-photon decay in the quantum jump process, we achieve complete suppression of odd photon emissions, resulting in high-purity, high-efficiency 2n-photon bundle emission characterized by photon bunching and bundle antibunching. Our results indicate that this scheme can effectively produce 2n-photon sources. Unlike previous methods that enhanced 2n-photon bundle purity via parity protection during unitary processes which required ultrastrong cavity-atom coupling, this study is the first to focus on parity protection during nonunitary processes to improve emission purity. This innovative approach not only relaxes the ultrastrong coupling condition compared to earlier schemes, but it also opens new research directions for enhancing N-photon bundle emission. Furthermore, this work has the potential to advance the fields of multiphoton physics and parity theory.